Comprehensive Analysis of Aerobic Exercise-Related Genes Identifies CDCA4 That Promotes the Progression of Osteosarcoma - Hao, Suyu; Zhu, Jun; Zhang, Xinyue; Qiu, Jingyue; Xuan, Qin; Ye, Liping (Frontiers in Genetics, 2021)
Background: Exercise has a positive impact on patients with osteosarcoma, improving function, reducing disability, maintaining independence and quality of life. Exercise may also directly affect the effectiveness of cancer treatment. Cell division cycle-associated protein 4 (CDCA4) is reported to function importantly during numerous human cancers development. Nevertheless, the details towards CDCA4 function are still to be investigated. Methods: This study comprehensively analyzed the GSE74194 database and obtained aerobic exercise-related genes. Protein-protein interaction network (PPI) and Gene Ontology (GO) analysis were performed on the differentially expressed genes (DEGs). Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and tumor genome atlas (TCGA) data mining were applied to measure aerobic exercise-related gene CDCA4 level in osteosarcoma tissue. We conducted lots of functional experiments to uncover CDCA4 function and its corresponding mechanism in osteosarcoma. Results: We screened a total of 547 DEGs related to aerobic exercise, of which 373 were up-regulated and 174 were down-regulated. PPI analysis revealed 90 genes that might play key roles. GO analysis showed that aerobic exercise-related DEGs were significantly enriched during the mitotic cell cycle, cell division, mitotic nuclear division and sister chromatid segregation, nuclear division, microtubule cytoskeleton organization involved protein, microtubule-based process, spindle organization, G2/M transition of mitotic cell cycle. Our results indicated that CDCA4 was increased in osteosarcoma tissues and cell lines, and its level had association with high mortality of osteosarcoma patients. Further studies revealed that absence of CDCA4 largely hindered osteosarcoma cancer cell proliferation, invasion and migration. Conclusion: Comprehensive bioinformatics analysis improves our understanding of the underlying molecular mechanisms of aerobic exercise on osteosarcoma. This provides evidence for the effect of aerobic exercise on CDCA4 expression. Our data suggested that CDCA4 could facilitate osteosarcoma development, and gave a hint that CDCA4 was a candidate target in the treatment of osteosarcoma, aerobic exercise might help the treatment and prognosis of patients with osteosarcoma.